Soil CO2 efflux in coffee agroforestry and full-sun coffee systems - Lopes, Vanessa Schiavon (2024)
Agroforestry systems may show low CO2 efflux, and CO2 efflux contributes to sustainability. This work aimed to evaluate the soil CO2 efflux in coffee plantations cultivated in agroforestry and full-sun systems during the winter in high-altitude tropical climate regions. The work was carried out at three family farms (RO, GI, and PA) in Minas Gerais, Brazil. Two treatments were established: coffee with and without trees, and 20 sampling spots for soil and gases. The air and soil temperatures in the agroforestry systems were lower than in the full-sun systems. The soil moisture content in agroforestry systems was higher than full-sun only on the GI. Except for the agroforestry systems in PA, all the other systems showed an increase in CO2 efflux with increasing soil moisture. This increase was more pronounced in agroforestry systems (RO), followed by full sun (RO). On the GI farm, this correlation was lower in the agroforestry system. Soil CO2 efflux was positively correlated with soil temperature and negatively correlated with total nitrogen, labile carbon and total organic carbon. Therefore, despite the microclimate stability promoted by the agroforestry systems in the winter, no decrease in the soil CO2 efflux was observed when compared to full sun systems.